The Other As a Source of Knowledge and a Reference Point for the Learning Adult - Semków, Jerzy (Journal of Education Culture and Society, 2019)
Aim. The aim of this paper is to discuss the possibility of adult learning by way of communicating with the representatives of other nations, cultures, and religions. Methods. The method used in the paper consists in the analysis of scholarly opinions wherein authors point out at the role of the Other human being in the process of our getting to know the world (from childhood: parents, neighbours – to the older age: people from different nations and cultures). The theory of learning introduced by Albert Bandura and Joanna Rutkowiak is utilized as a theoretical background. Results. The relation with the other can take many forms and fulfil different, albeit important in terms of education and functions. The other is a person who in numerous life situations becomes a source of knowledge for the learning adult, at the same time playing a role of a specific reference point. The recognition of the value of such resources acquires special meaning in the current situation wherein one can observe the emergence of attitudes of xenophobia and chauvinism. Moreover, learning through intercultural interactions can be seen as an effective way of gaining knowledge about the world of rapid changes. Conclusions. The paper concludes with the following questions: To what extent does the rising atmosphere of intolerance impoverish the cognitive sphere of the adult learner? In what way does the lack of acceptance of the Other destroy the field of sensitivity of the adult person? What are the prospects – given the current socio-political climate in Poland – and what kind of possibilities can be opened by the dialogical strategy of understanding Otherness?